Identification of double-stranded RNA-binding domains in the interferon-induced double-stranded RNA-activated p68 kinase. - Feng, G S (1992)
The double-stranded RNA (dsRNA)-binding domain of the human p68 kinase has been localized to the N-terminal half of the enzyme by using progressive deletion analysis and in vitro binding assays. To further define the domains responsible for binding to dsRNA, we cloned the mouse dsRNA-activated p65 kinase and used sequence alignment to identify conserved domains in the N-terminal region. Deletions in either of two 12-amino-acid-long and arginine- or lysine-rich regions abrogated binding to dsRNA. Moreover, in an in vivo growth inhibition assay in the yeast Saccharomyces cerevisiae, these mutants failed to exhibit a slow-growth phenotype.